PENGARUH METODE READING ALOUD TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS IV SD ADVENT VICTORY SORONG - Gladys Ansye Rangian; Muh Faizin; Jaharudin (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the effect of the Reading Aloud method on the reading comprehension ability of fourth-grade students at Advent Victory Elementary School in Sorong. The background of this research is the low ability of students to understand the content of reading passages, even tho they are technically able to read. The research approach uses a quantitative method with a One Group Pretest-Posttest Design, involving 15 students as the sample. The research instrument was a reading comprehension test administered before and after the implementation of the Reading Aloud method. The results of the paired sample t-test showed a calculated t-value of 9.68 > t-table 2.145 with a significance value of 0.000 < 0.05. This result indicates that the implementation of the Reading Aloud method significantly impacts the improvement of students' reading comprehension skills. This research confirms that Reading Aloud is an effective strategy for improving literacy and reading interest in elementary school students.